Identification of some novel amide conjugates as potent and gastric sparing anti-inflammatory agents: In vitro, in vivo, in silico studies and drug safety evaluation - KULABAŞ, NECLA; DANIŞ, ÖZKAN; OGAN, AYŞE; ERDEM, SAFİYE; KÜÇÜKGÜZEL, İLKAY (My University, 2023)
Today, usage of NSAIDs (nonsteroidal anti-inflammatory drugs) is very common. However, it has been proven by many studies that NSAIDs with free carboxylic acid group damage the GI (gastrointestinal) system. Our aim was to mask the acidic groups of NSAIDs to prevent or reduce their side effects while preserving their pharmacological effects. In this study, new amide derivatives of known NSAIDs, compounds 11–20, were synthesized to investigate their analgesic and anti-inflammatory effects using in vivo models. While compound 11 showed the most remarkable anti-inflammatory activity by 60.9% inhibition value at 200 mg/kg dose, compounds 11, 12, 15 and 18 had almost the same analgesic activity to that of acetylsalicylic acid (100 mg/kg) and flurbiprofen (100 mg/kg). In addition, all test compounds used at high dose (200 mg/kg, p.o) did not show any acute toxicity. COX-1 and COX-2 inhibition properties of all compounds were measured by biochemical methods and the interaction of the most active compounds with COX enzymes is elucidated by computer-assisted virtual screening methods. It was determined by in vitro enzyme inhibition studies that compound 11 and 13, synthesized from selective COX-1 inhibitors dexketoprofen and flurbiprofen, are selective COX-2 inhibitors. Moreover, compounds 11–13 were found to be non-mutagenic according to the mutagenicity assay using Salmonella TA98 and TA100 strains with and without metabolic activation. Finally, the prediction of ADMET profile and drug-likeness properties of compounds 11–20 were examined and the obtained results were evaluated.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; Analgesic effect; Anti-inflammatory effect; Cyclooxygenase (COX) inhibitors; Molecular modeling; Non-steroid anti-inflammatory drugs